من أصول النحو في الاستشهاد بالقراءات القرآنية في الرباعي من حروف المعاني - دباز, عبد الفتاح; عياض, محمد رضا (جامعة الوادي university of eloued, 2023)
يهدف هذا البحث إلى فهم فلسفة اللغة العربية, المتمثلة في أصول النحو وسيلةً لــــتتبع التعليل لدى علماء التوجيه للقراءات القرآنية، فلا يكتفى بالإعراب والوزن في دفع التعارض بين القياس اللغوي، وبين السماع الذي هو أصل لا ينازع؛ فالقراءة سنة متبعة وهي من السماع بمكان. وقد كانت نتائج البحث في النظر إلى العلاقة بين القياس اللغوي والقراءات القرآنية من حيث هي علاقة تناظر يعمل فيه الكلام العربي كلاًّ لا يتجزأ في الاستشهاد؛ لأن الأحرف السبعة جاءت للتيسير، ولا شك أنها من قبيل الفصيح الذي يقابله اعتبارُ ما خرج عن القياس اللغوي عند النحاة من القليل النادر والشاذ والبعيد عن الأفصح. This research aims to understand the philosophy of Arabic language represented in Arabic grammar principals, as a tool of following the justification at Quranic readings orienting scientists, it’s not enough to consider grammar and speech weight to get rid of the objection between linguistic analogy and the listening as an undisputed principal cause the reading is a followed usage. And the results of the research looking on the relation between linguistic analogy and Quranic reading was a symmetry relation where Arabic speech works as a whole indivisible in citation, because articles came to simplify and make it like literary, in the opposite count which came out of linguistic analogy at grammar scientists from the little rare and abnormal and far from the best literary
مقال
Keywords: القراءات ،القياس، الشاذ، النادر، المستعمل; Readings; Analogy; Abnormal; Rare; Used